A Comparison of Hiking Communities on the Appalachian and Pacific Crest Trails. (19th May 2022) - Fondren, Kristi M.; Brinkman, Richard
Abstract: Recent research has examined the long-distance hiking community on the Appalachian Trail (AT) and attempted to understand members of this leisure subculture in terms of their sociality and social practices. Using Gelder's subcultural perspective, we continue this line of research by comparing hikers' interactions and experiences on the AT to a second well-known long-distance hiking trail, the Pacific Crest Trail (PCT). Analysis of ethnographic field notes and interviews with 72 long-distance hikers suggests that while there are unique experiences associated with each trail, there is a more general long-distance hiking subculture. More specifically, the long-distance hiking subcultures on the AT and PCT are nested or geographically situated subcultures within a larger hiking subculture. This article contributes to scholarship on place attachment, place identity, and leisure subcultures by further examining the long-distance hiking community as well as the role of specific recreational settings in the formation of leisure subcultures and subcultural identities.